Examination of fetal growth trajectories following infertility treatment - Besharati, Melody (J Assist Reprod Genet, 2020)
PURPOSE: The objective of this retrospective cohort study was to compare fetal growth during the second and third trimesters for ovulation induction with intrauterine insemination (IUI), fresh embryo transfer (ET), frozen embryo transfer (FET), and spontaneous conception following infertility. METHODS: Three hundred ninety-five women with viable pregnancies confirmed at a single academic fertility center participated. All women achieved pregnancy either by treatment or spontaneously after a diagnosis of infertility. Inclusion criteria included autologous singleton pregnancies. Exclusion criteria included pregnancies from donor oocytes, twins, unavailable ultrasound data, and treatment methods with small number of participants. Primary outcomes of interest were head circumference (HC), abdominal circumference (AC), HC/AC ratio, and estimated fetal weight (EFW). Conditional growth curve models were created, and growth curves were selected for each outcome of interest. RESULTS: For ovulation induction with IUI, fresh ET, FET, and spontaneous conception, the slope analysis of growth curves for per-week growth rate of HC, AC, HC/AC ratio, and EFW demonstrated no difference. A subgroup analysis of fresh ET and FET groups, for same outcomes, also showed no difference. CONCLUSION: These findings contribute to the very limited literature on fetal growth trajectories following infertility treatment and suggest no significant differences in fetal growth for ovulation induction with IUI, fresh ET, FET, and spontaneous conception following infertility. It is possible there were no differences in growth trajectories between these conception methods because the majority of children born following infertility are of normal birth weight. While results are reassuring, further research with larger populations is warranted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-020-01785-8) contains supplementary material, which is available to authorized users.